Formação cultural de professores : perspectivas a partir da análise de ações educativas em museus da cidade de São Paulo - Sacuman, Jessica [UNIFESP] (2016)
This research has as a theme the relation among the areas of education, culture and teacher training and, specifically, the cultural training of early childhood education and early years of elementary school (childhood schools) in museums. This theme emerged from our trajetory on pedagogy course in the Federal University of São Paulo - School of Philosophy, Letters and Human Sciences (EFLCH) ? Guarulhos Campus. Making use of qualitative approach with literature review and document analysis, we analyzed the perspectives of cultural training and teacher training in two art museums of the state of São Paulo: museum of modern art (MAM) and art gallery of the state of São Paulo (PESP). Documents produced by educational sectors of both institutions were analyzed so that previous questions of this research were answered. From the readings of the theoretical framework and of the analysis of the documents produced in the museums, we considered that these institutions perform the cultural training of teachers of early childhood school (preschool). There were differences between the actions performed in each one of them. Starting off the considerations of triangular approach, we consider that MAM realize the formation actions according to this methodological approach, so in this way teachers have the possibility to learn the history of art, appreciate works of art and experience practical moments (artistic and creation). In PESP, the documents analyzed are focus in appreciation of art works and history of art, teachers do not have the chance of create directly in the cultural formation in this institution. However, PESP presents a specific material for small children, considering their time of living the childhood. Consequently, the materials complement each other, contributing for continuous cultural formation of professors and for the intersection between Education and Culture like spaces of education not to formal and increase the teacher?s cultural repertoire. In the concluding remarks we also emphasized the problem of neglecting the public social rights with good quality and has no cultural democratisation, tha has direct correlation with the cultural teacher training.